The Chinese of South-East Asia - Minority Rights Group (London : MRG, 1992)
With: Draft Declaration of the Rights of Persons Belonging to National or Ethnic Religion and Linguistic Minorities, as approved by the Commission on Human Rights at the 48th Session (Resolution 1992/16 of 21 Feb. 1992)
Keywords: Chinese in Southeast Asia